Inmegacity characterization: trends and realities. (17th July 2019) - Castillo, Julio Cesar; Goicochea, Elsa; Chong, Mario; Rodriguez, Michelle
Abstract : Purpose: In recent decades, there has been an important growth of Latin American cities; therefore, the demand for resources and services has increased for cities to function and meet the needs of their inhabitants. Latin American cities are growing rapidly and this process affects the quality of life of citizens. The purpose of this paper is to characterize the logistics of an area of the city of Lima, Peru; through the analysis of the practices of the last mile distribution, and in this way, contribute with information that can be used for decision-making and for the proposal of public policies that improve the efficiency of logistics operations in the area. Design/methodology/approach: Regarding the methodology applied, first, we identified the district to be analyzed using marketing information from the districts of Lima. Next, the authors collected information using forms following the methodology of the last Mile/Km 2 -MIT. Finally, the project planning finished in 15 days. Findings: It was found that most of the stores in the area are nanostores that sell diverse products, the community does not have parking lots or loading and unloading areas and the majority of deliveries are made to wholesalers and supermarkets. In addition, a relationship between business density and the traffic congestion was identified and taxis are the most widely used means of distribution of goods. Most of the streets do not have signage, they are mainly one-way and do not have exclusive routes for public transportation. Research limitations/implications: Due to not having georeference information about the specific stores location and statistics data about its suppliers, the research results may show a primarily scope. Based on the results, the authors are encouraged to do more research using data analytics as in the next steps. Practical implications: The paper reinforces the importance and challenge of working collaboration between suppliers, owners and local government. Social implications: The paper provides opportunities to create new policies, as well as an incentive plan for personal workers, suppliers and ecosolution proposals. Originality/value: Currently, as per the authors' knowledge, there is no varied literature that characterizes and analyzes the logistic profile of the districts of Lima city and serves as a basis for the implementation of solutions and public policies. Abstract : Objetivo: El objetivo de esta investigación es caracterizar la logística de un área de la ciudad de Lima, Perú; a través del análisis de las prácticas de la distribución de la última milla y, de esta manera, contribuir con información que se puede utilizar para la toma de decisiones y para la propuesta de políticas públicas que mejoren la eficiencia de las operaciones logísticas en el área. Diseño/metodología/enfoque: Con respecto a la metodología aplicada, primero, se identificó el distrito a analizar utilizando información de mercadeo de los distritos de Lima; a continuación, se recopiló información utilizando formularios siguiendo la metodología de la última milla/Km 2 -MIT; finalmente, la planificación del proyecto terminó en 15 días. Resultados: Se encontró que la mayoría de los establecimientos son pequeñas tiendas que venden productos diversos, no tienen estacionamientos o áreas de carga y descarga y la mayoría de las entregas se realizan a mayoristas y supermercados. Además, existe una relación entre la densidad comercial y la congestión de tráfico, siendo los taxis los medios de distribución más utilizados. La mayoría de las calles no tienen señalización, son de un solo sentido y no tienen carriles exclusivos para el transporte público. Estos hallazgos son relevantes para la implementación de políticas públicas para la mejora de la infraestructura y eficiencia de las operaciones logísticas. Originalidad/valor: Actualmente no existe una literatura variada que caracterice y analice el perfil logístico de los distritos de la ciudad de Lima y sirva de base para la implementación de soluciones y políticas públicas. Palabras clave Planificación, Planeamiento urbano, Distribución, Submegaciudades, Megaciudades, Urbanismo, Recursos Tipo de artículo: Artículo de investigación Abstract : Objetivo: O objetivo desta investigação é caracterizar a logística de uma área da cidade de Lima, Peru; através da análise das práticas de distribuição da última milha e, desta forma, contribuir com informações que possam ser utilizadas na tomada de decisão e pela proposição de políticas públicas que melhorem a eficiência das operações logísticas na área. Desenho/metodologia/abordagem: Com relação à metodologia aplicada, primeiro, o distrito a ser analisado foi identificado usando informações de marketing dos distritos de Lima; em seguida, as informações foram coletadas por meio de formulários seguindo a metodologia da última milha/Km 2 -MIT; finalmente, o planejamento do projeto terminou em 15 dias. Resultados: Constatou-se que a maioria das lojas comercializa diversos produtos, não possui estacionamentos ou áreas de carga e descarga e sendo a maioria das entregas realizadas para atacadistas e supermercados. Além disso, existe uma relação entre a densidade comercial e o congestionamento de tráfego, sendo os táxis os meios de distribuição mais utilizados. A maioria das ruas não possui sinalização, são de sentido único e não possuem pistas exclusivas para o transporte público. Essas constatações são relevantes para a implementação de políticas públicas para melhorar a infraestrutura e a eficiência das operações logísticas. Originalidade/valor: Atualmente não existe uma literatura variada que caracterize e analise o perfil logístico dos distritos da cidade de Lima e sirva de base para a implementação de soluções e políticas públicas. Palavras-chave Planejamento, Planejamento urbano, Distribuição, Sub megacidades, Megacidades, Planejamento urbano, Recursos Tipo de artigo: Artigo de pesquisa